2021
DOI: 10.3390/diagnostics11112101
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Myocardial Fibrosis, Strain Imaging and Collagen Biomarkers in Adults with Repaired Tetralogy of Fallot

Abstract: Background: We sought to assess the interplay between right ventricle (RV) fibrosis, biventricular dysfunction based on global longitudinal strain (GLS) analysis, and biomarkers such as Galectin-3 (Gal-3), procollagen type III (PCIII), and NTproBNP. Methods: We studied 35 adult patients with rToF. All patients underwent a cardiac magnetic resonance (CMR) scan including feature tracking for deformation imaging. Blood biomarkers were measured. Results: LGE RV was detected in all patients, mainly at surgical site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“… 70 The arrhythmogenic potential in adults after surgical correction of ToF could be attributed to the right atrial pressure overload (due to the right ventricular dysfunction); the tricuspid, mitral, or pulmonary regurgitation; and the atrial surgical scars in case of previous ventricular septal defect repair via right atriotomy. 71 , 72 The different types of ToF repair, including ventriculotomy, transannular patch, or palliative shunt, have not been associated with differences in the AF rate. 73 , 74 …”
Section: Achd Forms Treated With Af Ablationmentioning
confidence: 99%
“… 70 The arrhythmogenic potential in adults after surgical correction of ToF could be attributed to the right atrial pressure overload (due to the right ventricular dysfunction); the tricuspid, mitral, or pulmonary regurgitation; and the atrial surgical scars in case of previous ventricular septal defect repair via right atriotomy. 71 , 72 The different types of ToF repair, including ventriculotomy, transannular patch, or palliative shunt, have not been associated with differences in the AF rate. 73 , 74 …”
Section: Achd Forms Treated With Af Ablationmentioning
confidence: 99%
“…On the other hand, Dudnyk et al claimed that, even if children are completely asymptomatic in post-corrective surgery for CHD, their Gal-3 levels are still elevated and are associated with myocardial disfunction, depicted through modified tissue Doppler imaging measurements [ 113 ]. Another study conducted on adult patients confirmed that Gal-3 failed to reflect both left and right ventricle dysfunction in adult patients who had undergone surgical procedures for ToF repair at pediatric ages [ 114 ]. Furthermore, Gal-3 did not correlate with the hemodynamic parameters such as right atrial pressure or right ventricular end diastolic pressure in children undergoing transcatheter valve replacement for congenital pulmonary valve stenosis or insufficiency, unlike NT-proBNP and ST2 [ 115 ].…”
Section: Gal-3 As a Predictor Of Complications Associated With Chd Co...mentioning
confidence: 99%
“…Given that the method of performing the surgical correction has changed over time, from a transannular patch with a transventricular approach to that with a transatrial approach, the obvious consequence is that even the surgical era is also associated with risk of VT. Arrhythmias are the most important problem to be taken into consideration in TOF. It has been estimated that in the long-term follow-up of TOF patients, 30% of patients will have atrial arrhythmia and 10% will have complex ventricular arrhythmia, and the mortality risk triples after the third postoperative decade, with sudden cardiac death (SCD) being the most common cause of late mortality [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%